Sub-basal Corneal Nerve Plexus Analysis Using a New Software Technology. (September 2018) - Batawi, Hatim; Shalabi, Nabeel; Joag, Madhura; Koru-Sengul, Tulay; Rodriguez, Jorge; Green, Parke T.; Campigotto, Mauro; Karp, Carol L.; Galor, Anat
Abstract : Purpose: To study sub-basal corneal nerve plexus (SCNP) parameters by in vivo corneal confocal microscopy using a new software technology and examine the effect of demographics and diabetes mellitus (DM) on corneal nerves morphology. Methods: A Confoscan 4 (Nidek Technologies) was used in this cross-sectional study to image the SCNP in 84 right eyes at the Miami Veterans Affairs eye clinic. Images were analyzed using a new semiautomated nerve analysis software program (The Corneal Nerve Analysis tool) which evaluated 9 parameters including nerve fibers length (NFL) and nerve fibers length density (NFLD). The main outcome measure was the examination of SCNP morphology by demographics, comorbidities, and HbA1c level. Results: Interoperator and intraoperator reproducibility were good for the 9 parameters studied (Intraclass Correlations [ICCs] 0.73–0.97). Image variability between two images within the same scan was good for all parameters (ICC 0.66–0.80). Older individuals had lower SCNP parameters with NFL and NFLD negatively correlating with age (r=−0.471, and −0.461, respectively, P <0.01 for all). Patients with diabetes had lower mean NFLD 10987.6 μm/mm 2 (±3, 284.6) and NFL 1, 289.5 μm/frame (±387.2) compared with patients without diabetes (mean NFLD 15077.1 μm/mm 2 [±4, 261.3] and NFL 1750.0 μm/frame [±540.7]) ( P <0.05 for all). HbA1c levels in patients with diabetes were inversely correlated with NFL and NFLD (r= −0.568, and −0.569, respectively, P <0.05 for all). Conclusions: The Corneal Nerve Analysis tool is a reproducible diagnostic software technique for the analysis of the SCNP with confocal microscopy. Older age, DM, and higher level of HbA1c were associated with a significant reduction in SCNP parameters.